Measuring the Prevalence and Incidence of Low Back Pain Disorders Among American Workers in the Aerospace and Defense Industry. Issue 9 (September 2015) - Goetzel, Ron Z.; D'Arco, Malinda; Thomas, Jordana; Wang, Degang; Tabrizi, Maryam J.; Roemer, Enid Chung; Prasad, Aishwarya; Yarborough, Charles M.
<x xml:space="preserve">Abstract</x> Objective: To determine the prevalence and incidence of low back pain (LBP) among workers in the aerospace and defense industry and in a specific company. Methods: Claims and demographic data from the Truven Health MarketScan normative database representing more than 1 million workers were drawn from a group of 18 US benchmark companies and compared with one particular company, Lockheed Martin Corporation. Results: The prevalence of LBP in the MarketScan normative group was 15.6% in the final study year (2012), whereas the incidence of new cases was 7.2% and 7.3% in years 2011 and 2012, respectively. Compared with the normative group, the company's prevalence and incidence rates were lower. Women and older workers were more likely to experience LBP compared with men and younger workers. Conclusions: The analysis was used to inform the company's leadership about the health burden of the condition and evaluate alternative treatment options to prevent the incidences and reduce the prevalence of clinical back pain among workers.